2004
DOI: 10.1149/1.1793714
|View full text |Cite
|
Sign up to set email alerts
|

Novel Solid Polymer Electrolytes with Single Lithium-Ion Transport

Abstract: State-of-the-art poly͑ethylene oxide͒ ͑PEO͒-based polymer electrolytes have a t Liϩ much lower than 1; it is typically around 0.2-0.3. Thus, the development of single-cation-conductive, solvent-free polymer electrolytes is considered of prime importance for the progress of the technology of lithium batteries. Attempts mainly directed at immobilization of the anion in the polymer architecture have been reported in the past, but with only modest success because this approach generally depresses the conductivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
47
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 94 publications
(49 citation statements)
references
References 15 publications
1
47
1
Order By: Relevance
“…Interestingly, an increase of the transference number of lithium ions has been achieved by dispersing nanoparticles, or by dissolving crown ethers or other molecules with specific ionic interactions [48,87,88]. A completely different approach was suggested and investigated by Bruce et al which relies on ordered domains of PEO based electrolytes with fast transport of lithium ions along helix channels formed by the PEO backbone [89,90].…”
Section: Ionic Transference Numbersmentioning
confidence: 99%
“…Interestingly, an increase of the transference number of lithium ions has been achieved by dispersing nanoparticles, or by dissolving crown ethers or other molecules with specific ionic interactions [48,87,88]. A completely different approach was suggested and investigated by Bruce et al which relies on ordered domains of PEO based electrolytes with fast transport of lithium ions along helix channels formed by the PEO backbone [89,90].…”
Section: Ionic Transference Numbersmentioning
confidence: 99%
“…High energy density rechargeable lithium batteries are important to the development of several applications such as portable electronic devices; electric or hybrid cars still requires the optimization of some critical operational features with special concern directed toward those related to safety and design flexibility [1]. Conventional lithium batteries, liquid electrolyte make batteries unsafe due to electrolyte leakage and electrochemical instability due to the repeated oxidation/restoration reaction at the interface between the electrode and electrolyte [2].…”
Section: Introductionmentioning
confidence: 99%
“…Also of importance is the fact that the mobile anions involve in unwanted electrode reactions and reduce the active area of the electrode. Blazejczyk et al 8 achieved a lithium-ion transport number equal to 1 with an appreciable conductivity and suggested that an anion-trapping mechanism was induced by the calixarene additive. Blazejczyk et al 9 [4]pyrrole (p-6) containing two dipyrro-methane moieties and two p-phenylene units was synthesized as described earlier.…”
Section: Introductionmentioning
confidence: 99%